The seven rings - Roberts, Nora (Roberts, Nora. Lost bride trilogy, 2025)
"The #1 New York Times-bestselling author concludes her compelling Lost Bride trilogy as two women--one dead, one alive--prepare for a terrifying final showdown... Long ago, Arthur Poole built a grand house overlooking the turbulent ocean, in a Maine village that bore his name. Today, Sonya MacTavish lives in that house--a manor that has been cursed for generations. Within its walls, she has witnessed the deaths of seven brides and the thefts of seven wedding rings. And now, to break the curse and banish a malevolent spirit once and for all, a difficult task must be completed. After Sonya, her boyfriend, Trey, and their friends are forced to hear, see--and feel--the suffering of the house's many ghosts as their torment is reenacted by the evil presence, their bond only strengthens and their anger is renewed. Refusing to let her spirit be broken, Sonya searches each room for clues to her ancestors' hidden story, putting the picture together, unearthing small treasures, and uncovering the moments of joy that existed among the sorrows. She's determined to bring light to this haunted place--to fill it with people, with life and hope, once again. But the enemy in the black dress continues to hover, to come at her in frightening forms. They may be illusions--but illusions can be powerful enough to wound and kill. She feeds on fear, and lies are her weapon. This dark-hearted witch wants to be mistress of Poole Manor, at any cost. And Sonya will need to fight a battle across two realms to finally take possession of the house on the clifftop--and of her own future..."--